Paraganglioma admitting with stage-4 hypertensive retinopathy - Yılmaz, İsa and Özcan Sıkı, Fatma and Öztürk, Mehmet and Buğrul, Fuat and Çelik, Zeliha Esin and Arslan, Şükrü (The European Research Journal, 2023)
Paragangliomas and pheochromocytomas are rare tumors originating in chromaffin cells which are predominantly located in adrenal glands. This tumor is generally bilateral and much more rarely seen in pediatric patients. Sustained or paroxysmal hypertension is the most frequent sign of paragangliomas /pheochromocytoma. Here, we present a 15-year-old patient diagnosed with the complaint of blurred vision.